MARKETING STRATEGY OF TOFU PRODUCTION BUSINESS IN IMPROVING SALES PERFORMANCE IN PERCUT SEI TUAN DISTRICT - Riko Safriandi; Khairuna Utami; Abraham Ismail Pulungan; Nelfita Rizka S Depari; Emma Fadhilah (Prodi Agribisnis Fakultas Agro Teknologi Universitas Prima Indonesia, 2026)
This research aims to analyze the marketing strategies of tofu production businesses in improving sales performance in Percut Sei Tuan District, Deli Serdang Regency. The study employed a qualitative method with a case study approach involving five tofu factories: Wak Fendy, JW, Ega, Wak Ir, and Eza. Data were collected through interviews, observations, documentation, and questionnaires distributed to owners, employees, and customers. The data analysis utilized the SWOT framework to identify internal factors (strengths and weaknesses) and external factors (opportunities and threats), summarized into IFAS and EFAS matrices. The results revealed that the total IFAS score was 6.20 and EFAS score was 8.56, indicating that the tofu factories possess strong internal conditions and are capable of effectively leveraging external opportunities. The SWOT analysis places the business position in Quadrant I, suggesting an aggressive growth strategy. Recommended strategies include maintaining product quality, offering competitive pricing, expanding distribution networks, optimizing digital marketing, and strengthening customer relations. This study is expected to serve as a valuable reference for tofu entrepreneurs and local governments in formulating policies to support the development of small and medium enterprises (SMEs) in the food sector.